The effects of plyometric training with speed and weight overloads on volleyball players’ strength, power, and jumping performance - Ahmad Reza Iranpour; Mohammad Hemmatinafar; Javad Nemati; Mohsen Salesi; Hamed Esmaeili; Babak Imanian (PLoS ONE, 2025)
Background The principle of gradual overload is crucial in improving sports performance, yet the effects of combining speed and weight overloads in plyometric training remain understudied. Objective This study investigated the effects of plyometric training with speed and weight overloads on isokinetic strength, explosive power, and agility in volleyball players. Method Forty male volleyball players were randomly assigned to four groups: plyometric training (PT), plyometric training with speed overload (PTS), plyometric training with weight overload (PTW), and plyometric training with both speed and weight overload (PTSW). Each group completed a four-week plyometric training regimen. Performance metrics, including Sarjent’s jump height (SJH), Spike jump height (SPJH), Sheppard test (ShT), muscle voluntary isometric contraction (MVIC), rate of force development (RFD), absolute peak torque (PTQ), relative peak torque (RPT), and average power (AP) of knee extensors and flexors were measured before and after the intervention. Results SJH improved significantly in PTS (P = 0.012), PTW (P = 0.041), and PTSW (P = 0.001) compared to PT. SPJH showed substantial gains in PTS (P = 0.002), PTW (P = 0.001), and PTSW (P = 0.001) compared to PT. Average jump height and highest jump in ShT were also significantly higher in PTS, PTW, and PTSW (P < 0.05). Additionally, RFDext240°/s was enhanced considerably in PTS (P = 0.001) and PTSW (P = 0.001). Conclusion Based on the results, plyometric training with speed and weight overloads (PTSW) demonstrated superior enhancements in isokinetic strength, explosive power, and jumping performance. This combined approach is highly effective and significantly benefits male volleyball players, aiming to enhance their physical abilities.